A sub-grid scale model developed for the hexahedral grid to simulate the mass transfer between gas and liquid. (December 2021) - Cai, Kangbei; Huang, Guangyuan; Song, Yuchen; Yin, Junlian; Wang, Dezhong
Highlights: Develop a sub-grid scale model developed for the hexahedral grid. The sub-grid scale model can reduce the computational cost of bubble mass transfer simulation. Simulation of bubble mass transfer at high Péclet number. Abstract: The gas-liquid mass transfer is widely applied in many industrial applications. The mass boundary layer at the interface is usually much thinner than that of the momentum boundary. To numerical simulate the interfacial mass transfer, an ultra-fine grid is needed to resolve the thin mass boundary layer, while the computational cost is usually unacceptable. In this paper, a sub-grid scale model based on the geometric VOF method has been developed for the hexahedral grid, which can be used to calculate the mass transfer flux based on the mass boundary layer thickness. Furthermore, the convection flux near the interface is estimated by the mass boundary layer thickness and the geometric information rather than a numerical interpolation method which would induce significant numerical diffusion. The sub-grid scale model can reduce the demanding requirement of the mesh resolution and a coarse grid can be used to obtain a good result.